2014
DOI: 10.4334/jkci.2014.26.6.695
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Precast Concrete Beam-Column Connections Using Ductile Rod

Abstract: Precast concrete (PC) beam-column connections using ductile rods are proposed for earthquake zone. An existing beam-column connection, two PC specimens designed by considering failure modes and a conventional RC specimen were tested under cyclic loading to evaluate the seismic performance. The specimens were designed to satisfy the requirements of current design code. The variables are the yield strength of longitudinal reinforcing bars of PC beams. The test results showed that the proposed system applying sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…29 The bars also satisfied ACI 318-19 9 requirements for Grade 100 (690) bars used in earthquake-resistant special structural walls. 20,22,25 of interior beam-column joints with Grade 100 (690) threaded bars (with a relative rib area 28 of 0.18), the reinforcement used in this study had bar deformations similar to those common in the United States (the relative rib area 28 was 0.10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 The bars also satisfied ACI 318-19 9 requirements for Grade 100 (690) bars used in earthquake-resistant special structural walls. 20,22,25 of interior beam-column joints with Grade 100 (690) threaded bars (with a relative rib area 28 of 0.18), the reinforcement used in this study had bar deformations similar to those common in the United States (the relative rib area 28 was 0.10).…”
Section: Methodsmentioning
confidence: 99%
“…Table 4 reports that V j,m /V n,m was 0.77 for A and between 0.86 and 0.94 for B, C, and D. Lee et al 22 observed that connections with V j,m /V n,m ≤ 0.8, such as Specimen A, normally exhibit a response dominated by beam flexural hinging, and that joints with V j,m /V n,m close to but not exceeding 1.0, such as Specimens B, C, and D, normally exhibit a joint shear failure in drift cycles of 4 to 6% after beam-bar yielding. This is consistent with the extensive inclined cracking observed in B, C, and D after loading to a 4% drift ratio, described previously.…”
Section: Joint Shearmentioning
confidence: 99%
See 1 more Smart Citation